QUO VADIS PENYELAMATAN ARSIP STATIS ORGANISASI KEMASYARAKATAN (ORMAS) YANG DIBUBARKAN: Array - Rayi Darmagara (Arsip Nasional Republik Indonesia, 2017)
In Reference to the Government Regulation in Lieu of Law Number 2 Year 2017 on Law of Amendments Number 17 Year 2013 regarding Societal Organization which was enacted by the Parliament during the Plenary Meeting on October 24, 2017, the government is banning the societal organizations which are deemed against the ideology of “Pancasila”. On the contrary, as stated in the Law Number 43 Year 2009 on Records and Archives Administration, these organizations are one of the important pillars that hold function as a creating agency of archives. The archives created by the organizations have to be transferred to the archives institutions. It will be a problem in the future if the process of banning the organizations is done without rescuing the archives of these organizations. Without rescuing these archives, there would be a high possibility that this nation would lose one of the collective of memory because the archives of these organizations hold important role as a part of the journey of the nation. If the archives are not rescued, it will likely that the archives of these disbanded organizations would be destroyed or be taken by the personnel of the organizations as his/her own personal collection. The archives institutions are obliged to conduct archives management of the societal organizations. This includes not only for active organizations but also for the disbanded organizations. The archives of the societal organizations which have been banned also have historical value that need to be preserved and rescued. However, based on the regulations stipulated by the National Archives of the Republic of Indonesia (ANRI), the acts of preserving and rescuing the archives of these disbanded organizations cannot be done. It needs some good solutions, which can be in the form of policies/regulations as a guidance and legal foundation to rescue the archives.